Quantitative PCR Measurement of miR-371a-3p and miR-372-p Is Influenced by Hemolysis - Myklebust, Mette Pernille; Rosenlund, Benedikte; Gjengstø, Peder; Bercea, Bogdan Stefan; Karlsdottir, Ása; Brydøy, Marianne; Dahl, Olav (Frontiers in Genetics, 2019)
Cell-free microRNAs have been reported as biomarkers for several diseases. For testicular germ cell tumors (GCT), circulating microRNAs 371a-3p and 372-3p in serum and plasma have been proposed as biomarkers for diagnostic and disease monitoring purposes. The most widely used method for quantification of specific microRNAs in serum and plasma is reverse transcriptase real-time quantitative PCR (RT-qPCR) by the comparative Ct-method. In this method one or several reference genes or reference microRNAs are needed in order to normalize and calculate the relative microRNA levels across samples. One of the pitfalls in analysis of microRNAs from serum and plasma is the release of microRNAs from blood cells during hemolysis. This is an important issue because varying degrees of hemolysis are not uncommon in routine blood sampling. Thus, hemolysis must be taken into consideration when working with circulating microRNAs from blood. MiR-93-5p, miR-30b-5p and miR-20a-5p have been reported as reference microRNA in analysis of the miR-371a-373 cluster. We here show how these three microRNAs are influenced by hemolysis. We also propose a new reference microRNA, miR-191-5p, which is relatively stable in serum samples with mild hemolysis. In addition, we show how hemolysis can have effect on the reported microRNA levels in patient samples when these reference microRNAs are used in samples with varying levels of hemolysis.